Blood mercury levels and PCR-based GSTP1 and GSTT1 gene profiles in artisanal gold miners: A cross-sectional study - Wimpy, Wimpy; Silviani, Yusianti; Hidayati, Nur; Aribowo, Daffina Ramadhani Putri; Septiani, Erni Dwi; Masykuri, Mohammad (Journal of Environment and Sustainability Education, 2026)
Mercury (Hg) exposure from artisanal and small-scale gold mining (ASGM) remains a major public health concern, particularly in communities where mercury amalgamation is still widely practiced. Chronic mercury exposure is known to induce oxidative stress and may interfere with detoxification pathways involving glutathione S-transferase enzymes, including GSTP1 and GSTT1. This study aimed to assess blood mercury levels and PCR-based GSTP1 and GSTT1 gene profiles among artisanal gold miners in Central Java. A cross-sectional descriptive study was conducted using whole blood samples from 10 adult males, consisting of 5 artisanal gold miners and 5 non-miner controls. Blood mercury concentrations were measured spectrophotometrically, while GSTP1 and GSTT1 gene profiles were evaluated using polymerase chain reaction (PCR). Blood mercury levels in miners ranged from 20.244 to 67.987 µg/L, exceeding the recommended reference value of <20 µg/L, whereas control subjects showed levels below the threshold. PCR analysis demonstrated expected GSTP1 and GSTT1 bands in all control samples. In contrast, miner samples showed variations in PCR band patterns, including larger than expected amplicons for GSTP1 and absence of GSTT1 amplification in two samples, which may indicate altered gene profiles associated with mercury exposure. In conclusion, artisanal gold miners exhibited elevated blood mercury levels alongside variations in GSTP1 and GSTT1 PCR profiles. Although the small sample size limits definitive genetic interpretation, these findings suggest that combined biomonitoring of mercury burden and detoxification-related gene profiles may provide useful preliminary indicators for assessing susceptibility to mercury exposure in ASGM settings.